A Spanner in the Works of the Factory of Truth: The Wits Qualitative Methods Conference - Terre Blanche, Martin (PINS-Psychology in Society, 2026)
One of the principal fault lines psychologists have come to accept as a natural feature of their discipline is that which runs between two distinct sources of knowledge about the person: Quantitative "scientific" research and qualitative "clinical" insight. This dichotomy is of course not unique to academic psychology, but reproduces common-sense perceptions of the person as knowable through either objective measurement or subjective experience. While apparently in opposition, the subjective and objective modes of knowing are two sides of the same coin, together constituting the modern, autonomous individual. The fantasy of objective knowledge encourages us to treat an historically specific form of selfhood (the autonomous individual) as if it were a natural fact, on a par with material reality, while the fantasy of subjective understanding reconfirms this individual as the ultimate guarantor and source of meaning. What is rendered invisible are the political and ideological struggles through which particular forms of subjectivity come into being in the first place.